Performance of a novel LED lamp arrangement to reduce SNR fluctuation for multi-user visible light communication systems - Wang, Zixiong (2013)
This paper investigates the performance of our recently proposed LED lamp arrangement to reduce the SNR fluctuation from different locations in the room for multi-user visible light communications. The LED lamp arrangement consists of 4 LED lamps positioned in the corners and 12 LED lamps spread evenly on a circle. Our studies show that the SNR fluctuation under such a LED lamp arrangement is reduced from 14.5 dB to 0.9 dB, which guarantees that users can obtain almost identical communication quality, regardless of their locations. After time domain zero-forcing (ZF) equalization, the BER performances and channel capacities of 100-Mbit/s and 200-Mbit/s bipolar on-off-keying (OOK) signal with most significant inter-symbol interference (ISI) are very close to that of the channel without any ISI caused by this LED lamp arrangement.